Informed consent in community-based oral health research - Singh, Shenuka (The Journal of Forensic Odonto-Stomatology - JFOS, 2023)
The ethical principle of respect for persons presents multiple dimensions to stimulate debate around issues related to informed consent for participation, data management, confidentiality and privacy. The informed consent process is built on a continuum involving a comprehensive explanation of the proposed study; and the declaration of consent (the right to withdraw from at anytime from the study without any negative consequences). All research involving human participants carry a certain level of risk (physical or informational) and it is not possible for the researcher to know all the consequences of participation before a study commences. This presentation will focus around the key issues of information, consent’ and competence in relation to community-based oral health research and outlines some of debates in the informed consent process.